Empirical Relationships Between the Elastic Settlement of Rigid Rectangular Foundations and the Settlement of the Respective Flexible Foundations - Pantelidis, Lysandros (My University, 2021)
The problem of settlement of shallow foundations is among the most important ones in classical soil mechanics. And while for the settlement of flexible foundations elastic solutions are widely used, for rigid rectangular foundations where the actual contact pressure distribution is still unknown, the problem is approximated either analytically assuming a contact pressure distribution or semi‐empirically combining the theory of elasticity with experimental and/or numerical results. A third and often attractive choice is the use of simple empirical relationships or relevant tabulated values relating the elastic settlement of rigid foundations (ρR) with the settlement of the respective flexible foundations (e.g. at the center, ρCe). Reviewing the relathionships of this third approach, the author revealed serious lack of consesous between the various sources; for example, according to the literature, ρR ranges between 68 and 125% of ρCe, the time when it is well-known that ρR < ρCe. In this paper, comparison of the settlement of 210 rigid foundation cases derived from 3D elastic finite element analysis, with the settlement of the respective flexible foundations derived from the theory of elasticity, led to simple empirical relationships between ρR and ρCe as well as between ρR and ρAv (ρAv = average settlement of the flexible foundation) with coefficient of determination (R2) almost unity. The analysis showed that these relationships are largely independent of the aspect ratio of foundations and the thickness and Poisson’s ratio (ν) of the compressible medium, although separate relationships are given for ν = 0.5, slightly increasing R2. Finally, a correction factor for foundation rigidity is given exploting the known linear relationship that exists between the relative stiffness factor of foundations and settlement.
Keywords: Elastic settlement analysis; Empirical correlations; Flexible foundations; Foundation rigidity; Rigid foundations